ANTIMALARIALS PRESCRIPTION TO PATIENTS IN JOSINA MACHEL CENTRAL HOSPITAL. JANUARY-JULY 2014 - Mateus Sebastião João Fernandes; Boaventura Moura; Héctor Lara Fernández; Vladimir Calzadilla Moreira; Lúcia Gomes Fraga (Formifarma, LDA., 2015)
Malaria represents the main public health problem in Angola, being the leading cause of disease and death. The misuse of antimalarials can lead to an increase of drug resistance and undesired adverse reactions, among other issues, with a negative impact in patients and the National Health System. An observational, descriptive, cross-sectional study, of the Drug Use Study type, was conducted in patients with a confirmed diagnosis of malaria admitted at Josina Machel Central Hospital, to evaluate the quality of prescription of antimalarials. This prescription-indication study was conducted from January to July of 2014, in a sample of 151 patients admitted in the Medicine and Therapy Services. The adequacy of the prescription was assessed taking into account patients characteristics and the prescribed therapeutic regimen (drug, dose, posology and duration of treatment), using the therapeutic guidelines of the National Malaria Control Programme in Angola as reference. There was a high prevalence of inadequate prescriptions of antimalarials, which was observed in 70 out of 151 patients (46.4%). The inadequate prescription of antimalarials was more frequently observed in cases of complicated malaria and between patients admitted in the Medicine Services. The more frequent causes of antimalarials misuse were "unnecessary or inappropriate drug combinations" and "inadequate treatment". The drugs more commonly misused were Quinine IV and Artemether IM.